2008
DOI: 10.1016/j.neuroimage.2008.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental changes in verbal working memory load-dependency: An fMRI investigation

Abstract: Development of working memory (WM) aptitude parallels structural changes in the frontal-parietal association cortices important for performance within this cognitive domain. The cerebellum has been proposed to function in support of the postulated phonological loop component of verbal WM, and along with frontal and parietal cortices, has been shown to exhibit linear WM load-dependent activation in adults. It is not known if these kinds of WM load-dependent relationships exist for cerebro-cerebellar networks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
68
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 55 publications
13
68
1
2
Order By: Relevance
“…In addition, patients showed less activation in regions of left vlPFC but also in dmPFC regions (BA 9) including dorsal ACC (BA 32) and the rostral ACC/frontal pole (BA 32/10) compared to typically developing participants. These regions all form part of a working memory network (Braver et al, 1997;Bunge and Wright, 2007;Ciesielski et al, 2006;O'Hare et al, 2008;Rottschy et al, 2012) that has previously been identified in patients with MDD to function abnormally (Bench et al, 1993;Harvey et al, 2005;Matsuo et al, 2007;Vasic et al, 2009;Walter et al, 2007b). In contrast, during the DMTS task patients showed increased activation of right posterior medial regions including the precuneus (BA7) and the PCC (BA31).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, patients showed less activation in regions of left vlPFC but also in dmPFC regions (BA 9) including dorsal ACC (BA 32) and the rostral ACC/frontal pole (BA 32/10) compared to typically developing participants. These regions all form part of a working memory network (Braver et al, 1997;Bunge and Wright, 2007;Ciesielski et al, 2006;O'Hare et al, 2008;Rottschy et al, 2012) that has previously been identified in patients with MDD to function abnormally (Bench et al, 1993;Harvey et al, 2005;Matsuo et al, 2007;Vasic et al, 2009;Walter et al, 2007b). In contrast, during the DMTS task patients showed increased activation of right posterior medial regions including the precuneus (BA7) and the PCC (BA31).…”
Section: Discussionmentioning
confidence: 84%
“…The precuneus is involved in a variety of processes including visuo-spatial imagery, episodic memory retrieval, self-processing and consciousness (Cavanna and Trimble, 2006). In addition, activation in this region has been found to depend on working memory load (Jahn et al, 2012;O'Hare et al, 2008;Stollstorff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, in some studies researchers find a wider set of areas activated for children than in adults, 5 but in other studies the number of brain regions showing linear load dependency expands with increasing age. 6 Studies also show that children who exhibit better performance on cognitive tasks exhibit more activity in task-relevant brain regions, 7 although better performance is associated as well with fewer activated regions. 8 These results would benefit from a developmental framework that explains the global and less differentiated performance in younger children in terms of processing limits in mental/executive attentional capacity in younger children.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 99%
“…[17][18][19][20] Although the majority of functional neuroimaging research on WM has been conducted with adults, developmental studies suggest that children recruit similar cortical networks. [21][22][23][24][25][26] With regard to white-matter pathways underlying WM, the few studies conducted in healthy individuals have identified the involvement of both intra-and interhemispheric tracts. In addition to the superior longitudinal fasciculi (the major white-matter pathways connecting frontal and parietal cortices), [27][28][29][30] investigations of typically developing (TD) children have identified significant correlations between visual WM performance and development of white matter in left frontoparietal regions, as well as in the anterior corpus callosum (CC).…”
Section: Introductionmentioning
confidence: 99%